ANALISIS OPTIMALISASI PEMBIAYAAN AKAD QARDHUL HASAN DAN MUDHARABAH DI PERBANKAN SYARI’AH (STUDI KASUS BANK MUAMALAT KANTOR CABANG PEMBANTU MUARO BUNGO) - Iyud Iyud (Dinasti Review, 2022)
This research was conducted because from the perspective of financing various types of contracts at the MuaroBungo branch of Muamalat Bank, it looks not optimal. This research was conducted in order to answer the questions: 1) What is the mechanism for implementing the financing of the qardulhasan and mudharabah contracts at the muamalat bank branch of muaroBungo; 2) How is the implementation of mudharabah contract financing at the muamalat bank branch of muaroBungo; 3) How to optimize the financing of qardulhasan and mudharabah contracts at bank muamalat muaro Bungo branch. This research is a field research (field research). This study seeks to examine in depth the Analysis of Financing Optimization of QardulHasan and Mudharabah Contracts in Islamic Banking (Case Study of Muamalat Bank Muaro Bungo Sub-Branch Office. The results of this study indicate that: 1). The financing mechanism for the qardhulhasan contract is only given to employees, this is due to (a) the high level of congestion, (b) there is no guarantee from the customer so that the qardhulhasan contract tends to be problematic, (c) the number of customers who use the qardhulhasan contract is not appropriate with the provisions, (d) The customer already has a loan at another bank, so the bank is afraid that the customer's salary is not sufficient to pay the debt installments. 2). Mudharabah contract financing mechanism is determined by the bank with conditions that must be fulfilled by the customer by prioritizing Islamic values, risk Commonly faced by banks is the dishonesty of customers or users of funds that are not in accordance with the contract. Mudharabah contracts have the advantage of increasing profit sharing, besides being free of usury, it is the reason customers choose Islamic banks over conventional banks. 3). Analysis of Optimizing the Implementation of QardulHasan and Mudaraba Financing of Bank MuamalatMuaroBungo Branch, so that the implementation of the qardhulhasan contract is more optimal: (a) The bank must thoroughly analyze the characteristics of prospective customers and full supervision of Bank Muamalat Muaro Bungo branch on the use of funds, (b ) The bank must provide administrative costs so that employees or customers do not pay administration and the funds can be taken from infaq and shadaqah.